Assay for characterizing the recovery of vertebrate cells for adhesion measurements by single‐cell force spectroscopy. Issue 19 (10th June 2014) - Schubert, Rajib; Strohmeyer, Nico; Bharadwaj, Mitasha; Ramanathan, Subramanian P.; Krieg, Michael; Friedrichs, Jens; Franz, Clemens M.; Muller, Daniel J.
Abstract : Single‐cell force spectroscopy (SCFS) is becoming a widely used method to quantify the adhesion of a living cell to a substrate, another cell or tissue. The high sensitivity of SCFS permits determining the contributions of individual cell adhesion molecules (CAMs) to the adhesion force of an entire cell. However, to prepare adherent cells for SCFS, they must first be detached from tissue‐culture flasks or plates. EDTA and trypsin are often applied for this purpose. Because cellular properties can be affected by this treatment, cells need to recover before being further characterized by SCFS. Here we introduce atomic force microscopy (AFM)‐based SCFS to measure the mechanical and adhesive properties of HeLa cells and mouse embryonic kidney fibroblasts while they are recovering after detachment from tissue‐culture. We find that mechanical and adhesive properties of both cell lines recover quickly (<10 min) after detachment using EDTA, while trypsin‐detached fibroblasts require >60 min to fully recover. Our assay introduced to characterize the recovery of mammalian cells after detachment can in future be used to estimate the recovery behavior of other adherent cell types. Abstract : Cell recovery after detachment from tissue‐culture flasks is prerequisite for SCFS. We introduce an SCFS assay to quantitatively characterize this cell recovery. The cell recovery time depends on cell type and the detachment procedure. Our method introduced here to characterize cell recovery is generally applicable.